Changes in Metabolic Hormones in Malaysian Young Adults following Helicobacter pylori Eradication - Yap, T.W.C.; Leow, A.H.R.; Azmi, A.N.; Francois, F.; Perez-Perez, G.I.; Blaser, M.J.; Poh, B.H.; Loke, M.F.; Goh, K.L.; Vadivelu, J. (Public Library of Science, 2015)
Background More than half of the world's adults carry Helicobacter pylori. The eradication of H. pylori may affect the regulation of human metabolic hormones. The aim of this study was to evaluate the effect of H. pylori eradication on meal-associated changes in appetite-controlled insulinotropic and digestive hormones, and to assess post-eradication changes in body mass index as part of a currently on-going multicentre ESSAY (Eradication Study in Stable Adults/Youths) study. Methods We enrolled 29 H. pylori-positive young adult (18-30 year-old) volunteer subjects to evaluate the effect of H. pylori eradication on meal-associated changes on eight gastrointestinal hormones, using a multiplex bead assay. Changes in body mass index and anthropometric measurements were recorded, pre- and post-eradication therapy. Results Pre-prandial active amylin, total peptide YY (PYY) and pancreatic polypeptide (PP) levels were significantly elevated 12 months post-eradication compared with baseline (n = 18; Wilcoxon's signed rank test, p<0.05). Four of the post-prandial gut metabolic hormones levels (GLP-1, total PYY, active amylin, PP) were significantly higher 12 months post-eradication compared to baseline (n = 18; p<0.05). Following H. pylori eradication, the BMI and anthropometric values did not significantly change. Conclusions Our study indicates that H. pylori eradication was associated with long-term disturbance in three hormones (active amylin, PP and total PYY) both pre- and post-prandially and one hormone (GLP-1) post-prandially. Longer post-eradication monitoring is needed to investigate the long-term impact of the observed hormonal changes on metabolic homeostasis.